Islam tidak galakkan kahwin lewat - Mohd, Azizah (SINAR HARIAN, 2020)
This short article gives an opinion about the position of late marriage in Islam. The points given confined only to the answer of the interview question by Sinar Harian Journalist Mdm Liza Mokhtar. The issue basically focused on late marriage among Malaysians and suggestions on few ways to solve this problem.